PENGARUH EFFECTIVE TAX RATE, DEBT COVENANT DAN FIRM SIZE TERHADAP TRANSFER PRICING - Linda Widya Ningrum (Yayasan Kayyis Mulia Jaya, 2026)
The purpose of this study is to determine the effect of Effective Tax Rate, Debt Covenant and Firm Size on Transfer Pricing. This study was conducted on Food and Beverage companies listed on the Indonesia Stock Exchange for the period 2020-2024. The method used in this study is a quantitative method. The type of data used is secondary data in the form of published financial reports of Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2020-2024. Samples were collected using a purposive sampling method. The number of companies used as research samples was 21 companies, with observations for 5 years from 2020-2024, resulting in a sample of 105 samples. The analysis technique in this study used panel data analysis, coefficient of determination, f-test, t-test with the help of Eviews-12 software. The results of this study indicate that the effective tax rate, debt covenant, and firm size have a simultaneous effect on transfer pricing. Partially, the effective tax rate has no effect on transfer pricing. Debt covenant has no effect on transfer pricing, and firm size has an effect on transfer pricing. Keywords : Effective Tax Rate, Debt Covenant, Firm Size, Transfer Pricing.